The Relationship Between Metabolic Syndrome with Incidence of Stroke - Fila Fatmisua Chrisna; Santi Martini (Universitas Airlangga, 2016)
Stroke is a non-communicable disease that is influenced by many risk factors. Some risk factors for stroke have similarities with the criteria for metabolic syndrome, namely abdominal obesity, glucose intolerance, reduction of High-Density Lipoprotein (HDL) cholesterol, increased triglyceride levels, and insulin resistance. This study aims to determine the relationship between metabolic syndrome and the incidence of stroke. This type of research is analytic observational with a case-control design. The case group is stroke patients who are undergoing hospitalization at the Regional Public Hospital of Dr. M. Soewandhie Surabaya. The case group was 32 people and the control group was 32 people, randomly selected. The variables studied were age, sex, metabolic syndrome the first criteria, metabolic syndrome the second criterion, and metabolic syndrome the third criterion. The results showed that the majority of stroke patients in the age range of 51-75 years (78%). Chi-Square test results showed a significant relationship between the first criteria metabolic syndrome (abdominal obesity, triglyceride levels, and HDL cholesterol levels) p = 0.01 OR = 6.82 (95% Cl = 1.23-68.17) ) and the second criterion of metabolic syndrome (HDL cholesterol level, blood pressure, and fasting glucose level) p = 0.007 OR = 5.80 (95% Cl = 1.30-35.15) with the incidence of stroke. It is expected that people routinely carry out lipid profile checks and waist circumference measurements to detect metabolic syndrome and also the risk of stroke.